(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
Sickle cell disease (SCD) comprises an inherited blood disorder that is life long and affects many people globally. Despite progress in therapy, SCA is a considerable cause of mortality and morbidity. This study was designed to measure the immunological and inflammatory parameters of patients with sickle cell disease (SCD) and to found if there is any role of it in the pathogenicity of the disease. This study included A total of 32 patients, their ages ranged from 16 to 55 years patients with Sickle cell disease who have been evaluated during vaso occlusive crisis and had been followed up till they attained steady state, and there are 32 normal control subjects matched with patients in age and sex. In general there was elevation in all parameters the study were included in patients than control and particularly in crisis, despite the IgM value which was insignificantly decrease, but the statically significant elevation reported only in CRP, IgG, IgA.